What comes after the “legal transplants” An analysis of the current Brazilian criminal procedure in light of comparative law - Renato Stanziola Vieira (Revista Brasileira de Direito Processual Penal)
The present study aims to focus the comparative criminal procedure in the light of the well known expression of “legal transplants”. In this meaning here is said, at a first moment, about the actual stage of the science of comparative law. After that follow the possible critical aspects which can be remembered in countries of Latin America, including Brazil. At the end, with eyes at criminal procedure and authors who had shared attention to the theme of comparative criminal procedure, it is assumed a critical position related to the scenario of some legal reforms in the ongoing Brazilian criminal procedure.